Manual de seguridad industrial y salud ocupacional según la norma OHSAS 18001, para la Empresa de carrocerías metálicas reybuss del cantón Santo Domingo año 2014 - Carreño García, Darwin Javier (2015)
The first steps in the development of this manual industrial safety and occupational health diagnosis of the current situation of the company REYBUSS is made, identifying activities and unsafe conditions as to the risks and dangers that arise in the process of building bodies metal. The information obtained in this research is acquired directly from workers who work in the production area through surveys and interviews, and observations reached through fieldwork identifying risks in each of the mechanical and industrial processes running in the business rules and procedures for it to help forewarn the welfare and health of workers they are described. The manual safety and occupational health improves the working environment of the company REYBUSS taking necessary actions necessary for preventing risks of accidents and illnesses that may directly affect workers granting the direct labor of the company. The outcome of field research risks that occur in the process of construction of metallic bodies that affect humans and the environment was observed.